2002
DOI: 10.1016/s0008-6363(02)00497-2
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular oxygen utilization efficiency is impaired in chronic streptozotocin-diabetic sheep

Abstract: This is the first study to demonstrate that diabetes alters ventricular energetics in vivo. LV oxygen utilization efficiency is impaired as a consequence of decreased contractile efficiency and stroke work efficiency. Impaired efficiency of oxygen utilization may explain in part the increased sensitivity of the diabetic heart to ischemia and the accelerated deterioration of ventricular function in diabetic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 36 publications
1
8
1
Order By: Relevance
“…The decreased cardiac efficiency in hearts from STZadministered db/ϩ mice, manifested by an increase in unloaded MVO 2 , contrasts with data obtained with diabetic hearts from STZ-administered sheep (24), in which decreased cardiac efficiency was the result of impaired contractile efficiency with no change in unloaded MVO 2 . In fact, the slope of the PVA-MVO 2 relationship for STZadministered mouse hearts was the lowest (Table 3).…”
Section: Discussioncontrasting
confidence: 86%
“…The decreased cardiac efficiency in hearts from STZadministered db/ϩ mice, manifested by an increase in unloaded MVO 2 , contrasts with data obtained with diabetic hearts from STZ-administered sheep (24), in which decreased cardiac efficiency was the result of impaired contractile efficiency with no change in unloaded MVO 2 . In fact, the slope of the PVA-MVO 2 relationship for STZadministered mouse hearts was the lowest (Table 3).…”
Section: Discussioncontrasting
confidence: 86%
“…We observed reduced myocardial work efficiency in T2DM compared with lean controls. This observation is in line with data from animal models (50,61) and from obese humans (49,56,58) and augments the sparse human data evaluating this feature of myocardial function in human diabetes.…”
Section: E455 Myocardial Metabolic Flexibility In Type 2 Diabetessupporting
confidence: 84%
“…However, there are also studies showing no effect of STZ on LV systolic pressure [1,2,19,20]. Nevertheless, it is striking that the clear difference in maximum LV pressure development between STZ and SHAM hearts in vitro (Figure 3) stands in contrast to the absence of any differences among systolic, mean or diastolic pressures measured in vivo (Table 1).…”
Section: Discussionmentioning
confidence: 94%
“…In many studies of the energetics of the diabetic heart, the deterioration of cardiac performance has been linked to a reduction of cardiac efficiency [1-5]. But, some studies have reported an unchanged value in diabetic animals [6-9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation